2021
DOI: 10.1088/1361-6560/abf010
|View full text |Cite
|
Sign up to set email alerts
|

Atlas construction and spatial normalisation to facilitate radiation-induced late effects research in childhood cancer

Abstract: Reducing radiation-induced side effects is one of the most important challenges in paediatric cancer treatment. Recently, there has been growing interest in using spatial normalisation to enable voxel-based analysis of radiation-induced toxicities in a variety of patient groups. The need to consider three-dimensional distribution of doses, rather than dose-volume histograms, is desirable but not yet explored in paediatric populations. In this paper, we investigate the feasibility of atlas construction and spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…We found similar DIR uncertainty values for our selected brain structures, with slightly less deviation, most likely because of the rigidity of structures contained within the skull. Veiga et al found and values of 0.7 ± 1.0 mm and 2.9 ± 5.7 mm, respectively, for DIR of the central nervous system in children [27] . Although our was consistent with that of Veiga et al, we found a slightly higher ( Table 1 ).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…We found similar DIR uncertainty values for our selected brain structures, with slightly less deviation, most likely because of the rigidity of structures contained within the skull. Veiga et al found and values of 0.7 ± 1.0 mm and 2.9 ± 5.7 mm, respectively, for DIR of the central nervous system in children [27] . Although our was consistent with that of Veiga et al, we found a slightly higher ( Table 1 ).…”
Section: Discussionmentioning
confidence: 93%
“…Although our study is the first to evaluate the feasibility of the complete IBDM workflow in pediatric CT data, the spatial normalization step can be compared to previous CT-based studies implementing IBDM in adult cohorts of lung cancer patients [16] , [30] , [31] , head and neck cancer patients [19] and a recent study evaluating spatial normalization in data from children [27] . Beasley et al found a DIR uncertainty (SD of center of mass) of 4.0, 0.34 and 0.30 mm in the left–right, anteroposterior and superior-inferior directions for the muscles of mastication [19] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To apply the deformations between groups of subjects, we need to project the SVFs into the atlas space, in which all the SVFs have the same position and resolution. The atlas was obtained from a group‐wise registration which spatially normalized a cohort of patients [1] 16,31 . In the procedure of the projection, the planning CT (pCT) of each patient was the reference geometry, and the CT acquired during the first treatment week (CT t ) was registered to the pCT to produce vpt$\pmb {v}_{p\rightarrow t}$, where p stands for pCT and t stands for the week (in this case t=1$t=1$) when the weekly CT acquired.…”
Section: Methodsmentioning
confidence: 99%